2021
DOI: 10.1126/science.aba7202
|View full text |Cite
|
Sign up to set email alerts
|

Geometric squeezing into the lowest Landau level

Abstract: The equivalence between particles under rotation and charged particles in a magnetic field relates phenomena as diverse as spinning atomic nuclei, weather patterns, and the quantum Hall effect. For such systems, quantum mechanics dictates that translations along different directions do not commute, implying a Heisenberg uncertainty relation between spatial coordinates. We implement squeezing of this geometric quantum uncertainty, resulting in a rotating Bose-Einstein condensate occupying a single Landau gauge … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…In particular, E f /E i = (1 + s −1 Υ)/2 when Ω f → 0. The same result can be obtained directly from Formulas (165)-(167), if one uses solution (45) (with Ω instead of ω) and its consequencies:…”
Section: Non-adiabatic Evolutionmentioning
confidence: 67%
See 2 more Smart Citations
“…In particular, E f /E i = (1 + s −1 Υ)/2 when Ω f → 0. The same result can be obtained directly from Formulas (165)-(167), if one uses solution (45) (with Ω instead of ω) and its consequencies:…”
Section: Non-adiabatic Evolutionmentioning
confidence: 67%
“…Consequently, the adiabatic regime corresponds to values u 1, whereas the case of u 1 can be considered as a smooth analog of sudden jump. Note that function ( 75) is close to (45) for τ 1 and u 1. However, these functions do not coincide exactly.…”
Section: Inverse Linear Decrease Of Magnetic Fieldmentioning
confidence: 77%
See 1 more Smart Citation
“…The most exciting possibility is realizing fractional quantum Hall physics and observing non-abelian phases of matter [1]. A recent experiment at MIT [2] made an important step towards achieving this goal. They found that when rotating a Bose gas in an anisotropic trap, the resulting nonequilibrium dynamics can drive the atoms into the lowest Landau level, a pre-requisite for observing the quantum Hall effect.…”
Section: Introductionmentioning
confidence: 99%
“…Early cold atom experiments used rotating traps to mimic the effect of the external magnetic field needed to reach the FQH regime [19][20][21]. In this setup, first signatures of the bosonic Laughlin state at ν = 1 2 have been observed [22].…”
mentioning
confidence: 99%